Sequential and spatial letter reversals in adults with dyslexia during a word comparison task: demystifying the "was saw" and "db" myths. (3rd April 2021) - Peter, Beate; Albert, Andria; Panagiotides, Heracles; Gray, Shelley
ABSTRACT: Whether sequential and spatial letter reversals characterize dyslexia in children has been unclear, largely due to developmental variability of these errors in children with and without dyslexia. Here we demonstrate both types of reversals for the first time in adults with dyslexia (n = 22) but not in control adults (n = 20). Participants evaluated 576 word pairs that consisted of two identical words or two words that differed subtly, by categorizing them as same or different. Two subsets of word pairs differed in sequential (e.g. "two tow") and spatial (e.g. "cob cod") letter reversals. The adults with dyslexia were less accurate than the controls regarding both types of word pairs. Their accuracy during left/right letter reversals was lower, compared to both up/down letter reversals (e.g. "cub cup") and nonsymmetric letter similarities (e.g. "half halt"). Accuracy during left/right reversals was correlated with accuracy during sequential rearrangement in the word pair task as well as with a composite measure of sequential processing based on nonword repetition, nonword reading, and multisyllabic word repetition. It was also correlated with a composite measure of literacy skills. A subset of the dyslexia group who produced left/right errors during a rapid single letter naming task obtained lower accuracy than the dyslexia subgroup without such errors during both types of letter reversals, and their overall literacy skills were lower. We conclude that sequential and left/right letter reversals characterize a severe dyslexia subtype. These two types of reversal are associated, are part of a general deficit in sequential processing likely due to cerebellar deficits, and persist into adulthood.